Physical oceanography from glider mission IFM03_depl13 - Marcus Dengler; Peter Brandt; Gerd Krahmann (PANGAEA, 2021)
These gliders were deployed from R/V METEOR cruise M131 (8.10. to 11.11.2016). They carried turbulence and Nitrate probes in addition to the regular sensors. The gliders mission was related to the PREFACE project "Enhancing prediction of tropical Atlantic climate and its impacts" (http://preface.b.uib.no) funded by the European Union within the 7th Framework programme. PREFACE is combining European and African expertise in observations, modelling, and marine ecosystems to improve our understanding and capabilities to predict Tropical Atlantic climate and its impacts. The specific objectives of the gliders mission were related to work package (WP) 3 and 4 of the project. In WP 3, the Glider data contribute to determining seasonal and interannual variability of the mixed layer heat and fresh water budgets by quantifying air-sea fluxes and diapycnal, isopycnal and advective heat and freshwater fluxes in the eastern boundary upwelling systems and the Gulf of Guinea. In WP 4, the Gilder data contribute to monitoring variability along the southern hemisphere coastal wave guide.